Bring your own spectrum (BYOS) – A tiered architecture supporting flexible spectrum allocation - Madhulika Tripathi; Braden Phillips; Matthew Sorell (International Telecommunications Society (ITS), 2019)
In this paper we present an innovative framework suitable for the next generation of wireless spectrum allocation. We call our framework - Bring Your Own Spectrum (BYOS) - to highlight the Spectrum as a Service (SaaS) nature of the architecture that allows all participants to be potential spectrum owners. The BYOS framework has a tiered and flexible architecture that is technology-neutral and allows multiple trading and sharing formats among a varied array of buyers and sellers. To develop the BYOS framework, we tackled the spectrum allocation problem using a top down approach. We make use of a quasi-static model of spectrum allocation in which allocation is specific to the type of operators, to build a tiered architecture. The framework also introduces two other novel concepts - a usagebased trading unit that is common across both long and shorter terms and the token-bucket system (used in network traffic management) for managing competition. The process is automated by making use of smart contract over a public ledger based system.
Keywords: 330; spectrum allocation; public ledger; smart contract